ECG-induced Koebner phenomenon: images in clinical medicine - Streit, Enrico; Vogelgsang, Lena (The New England journal of medicine, 2017)
A 53-year-old man with psoriasis presented to the dermatology clinic with new psoriatic lesions on his chest where electrodes had recently been placed during electrocardiography.